Antibacterial Activities Of Green Silver Nanoparticles-strobilanthes Crispus (AgNP-SC) Against Clinically Important Bacteria - Rohazila Mohamad Hanafiah; Siti Nor Asma Musa; Siti Aisyah Abd Ghafar (UPM, 2024)
Non-Indexed Publication